2018
DOI: 10.14735/amko201835
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Checkpoint Inhibitors in the Treatment of Esophageal and Gastric Tumors – Overview of Studies

Abstract: SouhrnVýchodiska: Nádory žaludku a jícnu představují i přes současné pokroky v onkologické léčbě onemocnění se špatnou prognózou. Jedinou potencionálně kurativní léčbu představuje stále chirurgická resekce doplněná neoadjuvantní či adjuvantní chemoterapií/ chemoradioterapií. U generalizovaného onemocnění, na rozdíl od jiných nádorů, cílená terapie bohužel dosud nepřinesla větší posun s výjimkou trastuzumabu a ramucirumabu, jejichž účinnost je však relativně omezená. Imunoterapie přestavuje rychle se rozvíjejíc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Esophageal cancer are tumors with high mutation loads that have attracted considerable attention since the beginning of interest in ICIs. [ 20 ] In the clinical trial of KEYNOTE-028 and number ONO-4538-07/JapicCTI-No.142422, ICIs also showed promising antitumor activity and a manageable safety profile. [ 21 , 22 ] Phase II clinical study KEYNOTE-180 further confirmed the sustained efficacy and controllable adverse effects of Pembrolizumab in the third-line and above treatment of advanced esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer are tumors with high mutation loads that have attracted considerable attention since the beginning of interest in ICIs. [ 20 ] In the clinical trial of KEYNOTE-028 and number ONO-4538-07/JapicCTI-No.142422, ICIs also showed promising antitumor activity and a manageable safety profile. [ 21 , 22 ] Phase II clinical study KEYNOTE-180 further confirmed the sustained efficacy and controllable adverse effects of Pembrolizumab in the third-line and above treatment of advanced esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizimab, Nivolumab) enhancing antitumor T-Cell activity through the inhibition of immune checkpoints, like the programmed death-1 (PD-1) receptor [9] and improved survival in some solid tumors like malignant melanoma and non-small cell lung carcinoma [10][11][12][13]. First line and second line treatment of metastatic esophageal cancer with checkpoint inhibitors considering the PD1/PDL1 axis are currently tested in a Phase III evaluation with pembrolizumab (KEY-NOTE-062, KEYNOTE-061) [14] as well as nivolumab (CheckMate-577) in the adjuvant setting with various other approaches in all lines of therapy [15].…”
Section: Introductionmentioning
confidence: 99%